Broadband light-concentration with near-surface distribution by silver capped silicon nanowire for high-performance solar cells. (January 2015) - Li, Yingfeng; Li, Meicheng; Song, Dandan; Liu, Hong; Jiang, Bing; Bai, Fan; Chu, Lihua
Abstract: Silicon nanowire (SiNW) shows striking light-concentration ability and thus holds promising application potentials in photonic devices. However, its narrow working waveband strongly affects its performance over the entire visible spectrum. Here, a silver capped SiNW structure (Ag-cap/SiNW) is presented to broaden the working waveband of the pure SiNW. Discrete dipole approximation simulations show that, by this structure, the light-concentration waveband can be significantly broadened from 440–620 nm (pure SiNW) to 300–620 nm. Thus, using the Ag-cap/SiNW in the solar cell, the ideal photocurrent density can be enhanced 16% compared with that using pure SiNW. Furthermore, the concentrated light shows the feature of the strong near-surface distribution around the Ag-cap/SiNW. This distribution feature gives a reasonable explanation for the huge superiority of the radial junction SiNW solar cells to axial junction SiNW solar cells from optical aspect. Additionally, due to the intrinsic waveguide property of SiNW, this Ag-cap/SiNW also has great potential applications in photonic devices such as nanoscale optical biosensors and light-integrated-chips. Graphical abstract: Silver capped silicon nanowire presents two outstanding optical features. The first one is broadband light-concentration ability in waveband 300–620 nm, which makes the ideal photocurrent density of solar cell using this structure show 16% higher than that using pure silicon nanowire. The second feature is that the concentrated light shows strong near-surface distribution, which provides reasonable optical explanation for the superiority of radial over axial junction solar cells. This structure has potential applications for high-performance solar cells, as well as other optical devices. Highlights: Silver capped silicon nanowire shows significant broader light-concentration waveband than pure silicon nanowire, which can increase the ideal photocurrent density by 16% in solar cells. The concentrated light in the nanowire has strong near-surface distribution, which provides reasonable optical explanation for the superiority of radial over axial junction solar cells. This structure also has potential applications in other optical devices.